2013
DOI: 10.5114/aoms.2013.38670
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis/Systematic review Tumor necrosis factor-α antibodies (infliximab, adalimumab and certolizumab) in Crohn's disease: systematic review and meta-analysis

Abstract: IntroductionThis meta-analysis compares the effectiveness and safety of tumor necrosis factor α (TNF-α) antibodies (infliximab, adalimumab and certolizumab) with either a placebo or each of them in the treatment of Crohn's disease (CD).Material and methodsA systematic review of literature published up to November 2012 was performed and a meta-analysis of identified studies was carried out. We searched the following databases: PubMed, EMBASE, The Cochrane Library and others. Only randomized or clinical controll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
59
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(61 citation statements)
references
References 32 publications
(108 reference statements)
2
59
0
Order By: Relevance
“…The meta-analyses also confirm that, in CD patients who initially responded to biologics, these agents are useful in maintaining remission in these patients up to 56 weeks [104][105][106]. Typically, the likelihood of maintenance of remission compared to placebo was in the range of relative response rate of 1.78 (95 % CI 1.51-2.09).…”
mentioning
confidence: 51%
See 2 more Smart Citations
“…The meta-analyses also confirm that, in CD patients who initially responded to biologics, these agents are useful in maintaining remission in these patients up to 56 weeks [104][105][106]. Typically, the likelihood of maintenance of remission compared to placebo was in the range of relative response rate of 1.78 (95 % CI 1.51-2.09).…”
mentioning
confidence: 51%
“…In short-term treatment, anti-TNF antibodies were significantly better than placebo in healing and closure of fistulae with a relative response rate of 2.44 (95 % CI 1.13-5.28) [105]. Recent studies with longer-term follow up indicate that one third of enterocutaneous fistulae and up to two thirds of perianal fistulae heal with infliximab, with closure being associated with longer-term treatment [108,109].…”
Section: Infliximab and Other Anti-tumor Necrosis Factor Antibodies Amentioning
confidence: 99%
See 1 more Smart Citation
“…This position is supported by the observa tion that the TNF inhibitors certolizumab pegol (which is licensed in Canada and Europe for the treatment of AS, PsA and RA, but not inflammatory bowel diseases) and etanercept, neither of which induces ADCC, are less effective as induction therapy for patients with Crohn disease compared with monoclonal antiTNF anti bodies with a functionally active Fc region. 22,23 By contrast, other TNF inhibitors, such as adalimumab, golimumab, and reference inflixi mab, have proven efficacy in patients with inflammatory bowel diseases. Nevertheless, the observed differences in FcγRIIIa binding and induction of ADCC by CTP13 did not preclude Health Canada from extra polating data from studies in patients with RA and AS to the indications of PsA and plaque psoriasis.…”
Section: Reviewsmentioning
confidence: 94%
“…[22][23][24][25] However, randomized clinical trials found rates of serious adverse events to be similar between biologic agents and placebo, and a study of adalimumab in clinical practice found rates of adverse events consistent with clinical trials. 22,[28][29][30][31][32][33] The results of this real-world analysis found …”
Section: Concomitant Treatment For CD Patients Treated With Iv Versusmentioning
confidence: 99%